Topical applications effect of casein phospho peptide-amorphous calcium phosphate and sodium fluoride on salivary Mutans Streptococci in children - Fajriani Fajriani; Aini Dwi Handini (Dental Journal (Majalah Kedokteran Gigi), 2014)
Background: Dental caries is one of the major human diseases caused by Mutans Streptococci (MS). Topical application casein phosphopeptide–amorphous calcium phosphate (CPP-ACP) dan Sodium fluoride are often use in children and play a role in the caries prevention. Purpose: The aim of study was to determine the effect of casein phosphopeptide–amorphous calcium phosphate (CPP-ACP) and Sodium fluoride topical applications to the number of salivary MS colonies in children. Methods: This study using cross-over design with quase experiment time-series. The subjects were 30 children in range of age 6-12 years old that obtained with simple random sampling. The saliva samples of subjects were collected 3 times. First, saliva samples were taken before the treatment; second, after CPP-ACP topical application; third, after sodium fluoride topical application. Between the CPP-ACP and sodium fluoride treatments there was a one week wash-out period. After each treatment, saliva samples were taken twice, 15 and 30 minutes after topical applications respectively. After cultivation on specific agar, the colony number of salivary MS was determined by colony counting (Colony Forming Units-CFU). Results: There was no significant difference between topical application casein phosphopeptide – amorphous calcium phosphate (CPP-ACP) and Sodium fluoride in reducing the number of Streptococcus mutans. But topical application of Sodium fluoride tended to show more reduction than CPP-ACP. Conclusion: The topical application of CPP-ACP and Sodium fluoride could reduce the number of salivary MS in children. The effect of Sodium Fluoride was somewhat greater than CPP-ACP.Latar belakang: Karies gigi merupakan salah satu penyakit manusia utama yang disebabkan oleh Streptococcus Mutans (MS). Topikal aplikasi kasein phosphopeptide - amorf kalsium fosfat (CPP-ACP) dan sodium fluoride sering digunakan pada anak-anak dan berperan dalam pencegahan karies. Tujuan: Penelitian ini bertujuan untuk mengetahui pengaruh aplikasi kasein phosphopeptide - amorf kalsium fosfat (CPP-ACP) dan Sodium fluoride secara topikal terhadap jumlah koloni MS pada saliva anak. Metode: Penelitian ini menggunakan desain cross-over dengan percobaan Quase time-series. Subjek penelitian ini adalah 30 anak dalam rentang usia 6-12 tahun yang diperoleh dengan simple random sampling. Sampel saliva subjek dikumpulkan 3 kali. Pertama, sampel saliva diambil sebelum perlakuan; kedua, setelah aplikasi topikal CPP-ACP; ketiga, setelah aplikasi topikal sodium fluoride. Antara aplikasi CPPACP dan sodium fluoride ada periode wash-out satu minggu. Setelah perlakuan, sampel saliva yang diambil dua kali, 15 dan 30 menit setelah masing-masing aplikasi topikal. Setelah ditumbuhkan pada media agar yang spesifik, jumlah koloni MS ditentukan dengan cara hitung koloni (Colony Forming Unit-CFU). Hasil: Tidak ada perbedaan yang signifikan antara topikal aplikasi kasein phosphopeptideamorf kalsium fosfat (CPP-ACP) dan sodium fluoride dalam mengurangi jumlah Streptococcus mutans. Tetapi aplikasi topikal Sodium fluoride cenderung menunjukkan penurunan lebih banyak dari CPP-ACP. Simpulan: Aplikasi topikal dari CPP-ACP dan Sodium fluoride dapat mengurangi jumlah MS pada saliva anak. Pengaruh Sodium Fluoride sedikit lebih besar dari CPP-ACP.